1901 Ariz. Sess. Laws 1244-45 - (:unkn) unknown (My University, 1901)
Prohibited the sale or transfer of any firearms or toy pistols which discharge explosive substances to any minor under the age of fourteen. Violators guilty of a misdemeanor.
Keywords: TRANSFER - MINORS